2015
DOI: 10.1007/s00127-015-1089-z
|View full text |Cite
|
Sign up to set email alerts
|

What can patients do to facilitate shared decision making? A qualitative study of patients with depression or schizophrenia and psychiatrists

Abstract: There are various ways in which patients can facilitate SDM/play a more active role in decision making, with patients emphasizing being open and honest and psychiatrists emphasizing being active in the consultation. Interventions to increase active patient behavior may enhance SDM in mental health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
111
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(118 citation statements)
references
References 24 publications
(27 reference statements)
2
111
1
4
Order By: Relevance
“…This study identified patient-related barriers, such as symptoms, communicative difficulties, as well as clinician-related barriers, such as poor empathy and listening, and discounting patient concerns. In fact, no existing studies have explored the views and experiences of clinicians on the process of treatment decision-making in bipolar disorder , in contrast to several studies on depression (McMullen, 2012;Simmons, Hetrick, & Jorm, 2013) and schizophrenia (Farrelly et al, 2016;Hamann et al, 2015;Seale, Chaplin, Lelliott, & Quirk, 2006). However, this study did not ask specifically about treatment decision-making, and included only patient perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…This study identified patient-related barriers, such as symptoms, communicative difficulties, as well as clinician-related barriers, such as poor empathy and listening, and discounting patient concerns. In fact, no existing studies have explored the views and experiences of clinicians on the process of treatment decision-making in bipolar disorder , in contrast to several studies on depression (McMullen, 2012;Simmons, Hetrick, & Jorm, 2013) and schizophrenia (Farrelly et al, 2016;Hamann et al, 2015;Seale, Chaplin, Lelliott, & Quirk, 2006). However, this study did not ask specifically about treatment decision-making, and included only patient perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we choose the most commonly used definition of patient participation, referring to patient involvement in decision making about their health care [10, 12]. This way, patient participation, which includes behaviours such as providing information, asking questions and preparing for consultations, is an issue closely related to Shared Decision Making (SDM) [13]. SDM is defined as a collaborative approach in which clinicians and patients share the best available information when making clinical decisions, and where patients are supported to consider options to achieve informed preferences [14].…”
Section: Introductionmentioning
confidence: 99%
“…Fostering patient engagement and SDM in mental health care is, therefore, essential. More initiatives are needed to support the decisional capacity, participation and active behaviour of patients in treatment granting them more choice and control regarding their own mental health care, to provide a more equitable and collaborative working relationship and to enhance shared decision making [1, 4, 13, 32]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations